Identification of Post-translational Modifications on Odorant-Binding Protein Isoforms from Pig Olfactory Secretome by High-Resolution Mass Spectrometry: O-β-N-acetylglucosaminylation and Phosphorylation - Bouclon, Julien; Le Danvic, Chrystelle; Guettier, Elodie; Bray, Fabrice; Tokarski, Caroline; Rolando, Christian; Nagnan-Le Meillour, Patricia (Frontiers in Ecology and Evolution, 2017)
Odorant-Binding Proteins (OBP) are major players of perireceptor events in olfaction. Despite their importance, a molecular mechanism explaining their specificity for odors and pheromones has yet to be proposed. A new approach is provided by the analysis of the pig olfactory secretome that is mainly composed of OBP isoforms, generated from 3 gene products by two types of post-translational modifications (PTM): i) phosphorylation and ii) O--N-acetylglucosaminylation (O-GlcNAcylation), which are unusual for secreted proteins. Although both types of PTM can be demonstrated on OBP isoforms by specific antibodies, they have to be identified by mass spectrometry (MS), as localizing PTM sites and identifying PTM patterns can help predict binding affinities. In this paper, we report the identification of phosphorylation and O-GlcNAcylation sites on peptides coming from trypsin digestion of only OBP (sensu stricto) by nanoLC-nanoESI-HCD-MS/MS-Orbitrap. These PTM were not present on VEG and SAL. PEAKS software analysis of raw MS data allowed selecting spectra that were analyzed manually to identify PTMs. Four peptides corresponding to two different portions of OBP sequence were modified either by a phosphate group or by a hexNAc moiety. Due to the high energy used in HCD, the data did not allow precise localization of the modified sites. The new findings contribute to a better understanding of the mechanisms by which OBP isoforms could extend the binding repertoire of the secreted OBPs. Data are available via ProteomeXchange with identifier PXD007955.